Oprah Winfrey : media success story - Saidman, Anne. (Minneapolis : Lerner Publications Co., 1990)
Examines the life of the actress and talk show host, from her childhood on a farm in Mississippi to her achievements in broadcasting and film.
Keywords: Winfrey, Oprah -- Juvenile literature; Winfrey, Oprah; Television personalities -- United States -- Biography -- Juvenile literature; Motion picture actors and actresses -- United States -- Biography; Television personalities; Actors and actresses; Afro-Americans -- Biography; Women -- Biography